Talking about War: dialogues in World War One novels - Sabine Bastian; Thomas Sähn (Linguistica)
This article discusses problems involved in the literary representation of argot and spoken language in the context of the First World War based on the analysis of a multilingual corpus including the French novel Le Feu, written by Henri Barbusse in 1916, its German version, Das Feuer, translated by Leo von Meyenbourg in 1918, as well as the German novel Im Westen nichts Neues, written by Erich Maria Remarque in 1929, and its French translation À l’Ouest, rien de nouveau by Alzir Hella and Olivier Bournac published the same year.